2017
DOI: 10.1177/0961203317703494
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Pneumocystis pneumonia in hospitalized patients with systemic lupus erythematosus: review of a clinical data warehouse

Abstract: Objective In the era of powerful immunosuppression, opportunistic infections are an increasing concern in systemic lupus erythematosus. One of the best-studied opportunistic infections is Pneumocystis pneumonia; however, the prevalence of Pneumocystis pneumonia in systemic lupus erythematosus is not clearly defined. This study evaluates the prevalence of Pneumocystis pneumonia in hospitalized systemic lupus erythematosus patients, with a focus on validating the Pneumocystis pneumonia and systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…However, we think that regular quality control surveys of NHIRD among all medical facilities by the BNHI has much improved the accuracy of coding in NHIRD [27], and bias attributed by the misclassification was hence minimised. Additionally, the prevalence of PCP infection in the present Taiwanese research was quite similar to those in other studies [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…However, we think that regular quality control surveys of NHIRD among all medical facilities by the BNHI has much improved the accuracy of coding in NHIRD [27], and bias attributed by the misclassification was hence minimised. Additionally, the prevalence of PCP infection in the present Taiwanese research was quite similar to those in other studies [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…However, our method allowed a higher sensitivity for identifying all patients with SLE. 10 The true prevalence of PML in SLE, RA, HIV and renal transplants therefore can only be estimated using this method to identify patients. In addition, given the retrospective nature of our study, patients with PML who were not clinically identified with the JC virus infection may not have been included.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SLE were identified using ICD-9 code 710.0 or 695.4, an alternative SLE diagnosis code, which has been verified with chart review. 10 The use of an SLE ICD code from even a single hospitalisation allowed a higher sensitivity for identifying all patients with SLE and PML, with a 66% positive predictive value (PPV) for SLE in our cohort. 10 A thorough chart review allowed for confirmation of SLE with PML diagnoses.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The resultant immunosuppression increases the risk of opportunistic infections. However unlike most opportunistic infections, pneumocystis pneumonia (PCP) has a low prevalence of 0.45% in immunocompromised SLE patients (7). Lower lymphocyte count right before the onset of PCP and the higher dose of steroid therapy along with depressed CD4+ counts are considered possible risk factors for the development of PCP infection in SLE patients (8).…”
Section: Discussionmentioning
confidence: 99%